2021
DOI: 10.3233/jad-200909
|View full text |Cite
|
Sign up to set email alerts
|

Lower Levels of Education Are Associated with Cognitive Impairment in the Old Order Amish

Abstract: Background: Lower education has been reported to be associated with dementia. However, many studies have been done in settings where 12 years of formal education is the standard. Formal schooling in the Old Order Amish communities (OOA) ends at 8th grade, which along with their genetic homogeneity, makes it an interesting population to study the effect of education on cognitive impairment (CI). Objective: The objective of this study was to examine the association of education with cognitive function in individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
2
13
0
1
Order By: Relevance
“…These occupations and life experiences could allow for additional non-formal education and practice with visuospatial tasks, resulting in a cognitive reserve specific to these visuospatial processes. This would be similar to evidence that links years of formal education with cognitive reserve, which protects against neurodegenerative disease (Farfel et al, 2013;Lövdén et al, 2020;Luerding et al, 2016;Ramos et al, 2021).…”
Section: Discussionsupporting
confidence: 73%
“…These occupations and life experiences could allow for additional non-formal education and practice with visuospatial tasks, resulting in a cognitive reserve specific to these visuospatial processes. This would be similar to evidence that links years of formal education with cognitive reserve, which protects against neurodegenerative disease (Farfel et al, 2013;Lövdén et al, 2020;Luerding et al, 2016;Ramos et al, 2021).…”
Section: Discussionsupporting
confidence: 73%
“…Women were 58.3% of the sample. Individuals were residents of Amish communities in Ohio (Holmes County) and Indiana (Adams, Elkhart, and LaGrange counties) and recruited as previously described by Pericak-Vance et al (1996), Hahs et al (2006), Edwards et al (2013), Edwards et al (2014) and Ramos et al (2021). This is part of a population-based study of aging and age-related phenotypes such as AD performed by researchers from the University of Miami and Case Western Reserve University after Institutional Review Board (IRB) review and approval.…”
Section: Study Populations and Clinical Assessmentmentioning
confidence: 99%
“…A second strategy to improve power and reduce heterogeneity is to study a genetically homogenous population such as the Amish (Hahs et al, 2006). The Amish in the United States live in relatively genetically isolated communities (Hahs et al, 2006); members of these communities have participated in longitudinal studies of aging, cognition, and cognitive impairment for over two decades (Pericak-Vance et al, 1996) (Hahs et al, 2006) (Edwards et al, 2011) (Cummings et al, 2012) (Edwards et al, 2013) (D'Aoust et al, 2015) (Ramos et al, 2021) which have identified sibships with both individuals with CI and siblings that are cognitively unimpaired (CU). Our hypothesis is that individuals that are CU carry genetic variants that delay AAO of CI in spite of having an increased risk due to advanced age and family history of CI in a sibling.…”
Section: Introductionmentioning
confidence: 99%
“…These studies show that the age and gender differences of cognitive impairment were obvious, the cognitive impairment of the female elderly is more serious than that of the male, and the cognitive impairment of the older elderly is more serious than that of the younger elderly ( 15 , 16 ). And now there's evidence that the higher the education level or the longer duration of education they have, the lower chance of cognitive impairment happens in older adults, and vice versa ( 17 , 18 ). These factors were also relevant to cognitive impairment such as behavioral and lifestyle factors such as diet and exercise.…”
Section: Introductionmentioning
confidence: 99%